METHODS OF SEARCHING ELECTRONIC EDUCATIONAL RESOURCES RELATED TO SCIENCE ON THE INTERNET (Web of Teachers: Inderscience Research, 2024)
Professional development requires a great responsibility to work with students on a logical basis of integrated pedagogical processes, to provide them with educational innovations and to achieve development.